The Non-receptor Tyrosine Kinase Pyk2 in Brain Function and Neurological and Psychiatric Diseases - de Pins, Benoit; Mendes, Tiago; Giralt, Albert; Girault, Jean-Antoine (Frontiers in Synaptic Neuroscience, 2021)
Pyk2 is a non-receptor tyrosine kinase highly enriched in forebrain neurons. Pyk2 is closely related to focal adhesion kinase (FAK), which plays an important role in sensing cell contacts with extracellular matrix and other extracellular signals controlling adhesion and survival. Pyk2 shares some of FAK’s characteristics including recruitment of Src-family kinases after autophosphorylation, scaffolding by interacting with multiple partners, and activation of downstream signaling pathways. Pyk2, however, has the unique property to respond to increases in intracellular free Ca2+, which triggers its autophosphorylation following stimulation of various receptors including glutamate NMDA receptors increases Pyk2 autophosphorylation. Pyk2 is dephosphorylated by the striatal-enriched phosphatase (STEP) that is highly expressed in the same neuronal populations. Pyk2 localization in neurons is highly dynamic, and altered following stimulation, with post-synaptic and nuclear enrichment. As a signaling protein Pyk2 is involved in multiple pathways resulting in sometimes opposing functions depending on experimental models. Thus Pyk2 has a dual role on neurites and dendritic spines. With Src family-kinases Pyk2 participates in postsynaptic regulations including of NMDA receptors and is necessary for specific types of synaptic plasticity and spatial memory tasks. The diverse functions of Pyk2 are also illustrated by its role in pathology. Pyk2 is activated following epileptic seizures or ischemia-reperfusion and may contribute to the consequences of these insults whereas Pyk2 deficit may contribute to the hippocampal phenotype of Huntington’s disease. Pyk2 gene, PTK2B, is associated with the risk for late-onset Alzheimer’s disease. Studies of underlying mechanisms indicate a complex contribution with involvement in amyloid toxicity and tauopathy, combined with possible functional deficits in neurons and contribution in microglia. A role of Pyk2 has also been proposed in stress-induced depression and cocaine addiction. Pyk2 is also important for the mobility of astrocytes and glioblastoma cells. The implication of Pyk2 in various pathological conditions supports its potential interest for therapeutic interventions. This is possible through molecules inhibiting its activity or increasing it through inhibition of STEP or other means, depending on a precise evaluation of the balance between positive and negative consequences of Pyk2 actions.